THE APPLICATION OF USES & ACTIVITIES AND ACCESS & LINKAGES IN PLACEMAKING THEORY AND THE IMPLEMENTATION OF THE HIGHEST AND BEST USE METHOD FOR DETERMINING THE OPTIMAL NEW FUNCTION OF THE EX-BORSUMIJ SITE, JALAN HINDU, MEDAN - Muhammad Randi Ashifa; Isnen Fitri; Basaria Talarosha (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The ex-Borsumij site located on Jalan Hindu, Medan is part of the historic Kesawan area and has significant cultural and economic value. However, the site remains abandoned and underutilized. This study aims to determine the best adaptive reuse strategy for this heritage asset through a placemaking approach, focusing on Uses & Activities and Access & Linkages, and evaluating alternatives using the Highest and Best Use (HBU) method. The research applies a quantitative approach using surveys and feasibility analysis, including NPV, IRR, PI, and Payback Period. Data were obtained from 125 respondents comprising local residents, visitors, government stakeholders, and potential investors. Results show that the restaurant and café function yields the highest financial feasibility (NPV: Rp 4.43 billion; IRR: 13.89%; PI: 1.22; Payback: 5 years 5 months). The study concludes that adaptive reuse as a food and beverage space is the most optimal function, balancing economic return and cultural preservation.